2021
DOI: 10.11646/zootaxa.4974.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Ceriodaphnia smirnovi (Crustacea: Cladocera), a new species from the Mediterranean Region, and a phylogenetic analysis of the commonest species

Abstract: Species of the genus Ceriodaphnia Dana, 1853 (Crustacea: Cladocera: Daphniidae) are present in the plankton of many freshwater bodies all around the World. However, the taxonomy of the genus is still poorly developed. Most species have been described in the nineteenth century and data on their morphology and distribution should be revised according to current standards. Currently, due to lack of reliable morphological and genetic data, almost all nominal species of Ceriodaphnia are considered as species groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 916 publications
(16 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…The sequencing of 40 individuals together with 100 sequences retrieved from public databases gave rise to a phylogenetic tree based on 140 sequences, which showed the existence of 13 different clades. Twelve of these clades were already identified by Alonso et al (2021) (see Figure 15) and 10 corresponded to the currently described species. One clade ( Ceriodaphnia sp.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…The sequencing of 40 individuals together with 100 sequences retrieved from public databases gave rise to a phylogenetic tree based on 140 sequences, which showed the existence of 13 different clades. Twelve of these clades were already identified by Alonso et al (2021) (see Figure 15) and 10 corresponded to the currently described species. One clade ( Ceriodaphnia sp.…”
Section: Resultsmentioning
confidence: 63%
“…This is further corroborated by the ASAP analysis, which identified with a high level of confidence three putative groups within the COI dataset of C. smirnovi . Alonso et al (2021) also found large intraspecific variability (>7% for COI) in other groups of Ceriodaphnia (i.e. C. megops Sars, 1862; C. cornuta Sars, 1885 /C.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations